A vida por um trabalho: população estrangeira e ilegal na Espanha - Márcia Siqueira de Carvalho (Confins)
The data of the census had disclosed a profile of the foreign population in Spain, had confirmed some impressions and had undone others. They also reflect the inequality in the distribution of the demographic increases in the territory of that country, with the prominence for the Mediterranean coast, the region of Catalonia (Northeast of the country) and in the city of Madrid and the outskirts, while she had population loss in the interior and the region north. The weight of the foreign population in the total population of Spain grew of 7,0% in 2004 for 8,5% in 2005. Despite the difficulty in the analysis of the population data in relation to the legalized foreigners and the illegal ones, this trend will not be reverted so early. Sectors of the Spanish economy depend on immigration, legal or not. Caixa Catalunya, financial entity of this independent community, esteem that 50% of the growth of the Catalan GIP in the last years must it the immigration phenomenon.